Association between physical activity and major adverse cardiovascular events in northwest China: A cross-sectional analysis from the Regional Ethnic Cohort Study - Wang, Yutong; Liu, Huimeng; He, Dandan; Zhang, Binyan; Liu, Yezhou; Xu, Kun; Cao, Suixia; Huo, Yating; Liu, Jingchun; Zeng, Lingxia; Yan, Hong; Dang, Shaonong; et al. (Frontiers in Public Health, 2022)
Background: To examine the association between daily physical activity (PA) and major adverse cardiovascular events (MACEs) in northwest China. Methods: The data in this analysis were part of the baseline survey of the Regional Ethnic Cohort Study in Northwest China from June 2018 to May 2019 in Shaanxi Province. This study used standardized self-reported total physical activity (continuous and categorical variables) and self-reported outcomes of MACEs. All analyses were conducted using the logistic regression model and stratified by age, sex, body mass index (BMI), and region. The dose-response relationships were assessed with a restricted cubic spline. Results: The average level of total PA was 17.60 MET-h/d. Every increase of four MET-h/d of total PA was associated with a lower risk of MACE (adjusted OR=0.95 [95% CI, 0.93 0.98]). Compared with participants in the bottom quartile of total PA, a lower risk of MACEs was observed in the top quartile group (≥23.3 MET-h/d, 0.68 [0.55 0.83]). Stratified analyses showed similar results in males, females, participants over 45 years old, participants in the rural region, and normal weight range participants (BMI<24 kg/m2). Total participants also observed a dose-response relationship after adjusting for socioeconomic and lifestyle factors. Conclusions: A higher level of PA was associated with a lower MACE risk. Future research should examine the longitudinal association of prospectively measured PA and the risk of MACEs.